Distance Learning Experience in the Context of Globalization of Education - Nikolaevna Poddubnaya, Tatyana (2021)
Today, the digitalization of education is one of the main tasks of the state social policy and an urgent sphere of life in modern society. At the beginning of 2020, the spread of COVID-19 forced educational institutions to introduce urgently all levels of distance learning technologies focused on the possibility to learn remotely and in real-time. The research focuses on the need to create an effective mechanism for organizing distance learning in the context of the globalization of education. The purpose of the research is to reveal the experience of distance learning in the context of globalization of education (based on the analysis of using the online learning platform Moodle). The results of the research reveal the prerequisites for the popularization of distance learning technologies in the practice of educational institutions, present the experience of using Moodle in the university educational process and determine the prospects of distance learning in educational practice.